Last tango in Halifax. Season two [videorecording (DVD)] - Jacobi, Derek; Reid, Anne; Lancashire, Sarah, 1964-; Walker, Nicola ([Publisher not identified], 2014)
"Award-winning comedy drama and PBS favorite returns for a second season as the two childhood sweethearts work to finally make a life together. After Alan's near fatal heart attack, he and Celia decide to marry secretly - but how will their daughters react? Uptight Caroline and rebellious Gillian discover they actually quite like each other, but will the fact Gillian spent a night with Caroline's ex-husband John jeopardize the stepsisters' fledgling friendship? As secrets from the past come tumbling out and family members adjust to changing relationships, can Alan and Celia find the long-awaited happiness they deserve?"--Container.